History of the world map by map - Snow, Peter (London Dorling Kindersley Limited, 2018)
With more than 140 detailed maps, this book is more than a historical atlas. The maps themselves tell the story of pivotal episodes in world history, from the first human migrations out of Africa to the race for space. Purpose-made regional and global maps present the history of the world in action, charting how events traced patterns on land and ocean - patterns of exploration, discovery, or conquest that created empires, colonies, or theatres of war. Thoughtful organization of information will help you follow the story of civilizations through ancient, medieval, and modern times. But not every page is full of maps. At key points in History of the World Map by Map, broad, sweeping introductions provide a chance to step back and look at entire periods, such as World War 2, or to explore overarching themes, such as the Industrial Revolution. Picture spreads, meanwhile, focus on epoch-defining moments or developments, such as fascism and communism, and the invention of printing.
Includes index.
Keywords: Historical geography; World history -- Maps